(untitled) (American Journal of Technology and Applied Sciences, 2025)
The article examines the phenomenon of struggle as an integral part of human activity. Various aspects of wrestling are analyzed, from martial arts to social and historical confrontations. Special attention is paid to the role of struggle in shaping character, strengthening the spirit and achieving goals. It also examines strategies and tactics used in martial arts, sports, and life in general. The article emphasizes the importance of willpower, perseverance and the ability to overcome difficulties on the way to victory.